Comparative analysis of Pn full-waveform inversion and travel-time tomography in imaging upper mantle azimuthal anisotropy - Lu, Bing; Bao, Xueyang; Sun, Yao-Chong; Zhang, Wei (Frontiers in Earth Science, 2026)
Conventional Pn-wave imaging techniques, typically based on the ray theory, rely on Pn travel times to resolve the 2-D velocity and azimuthal anisotropy structures of the uppermost mantle. However, these approaches neglect the finite-frequency effects of wave propagation, thereby being limited in resolution and accuracy in resolving anisotropy structures. With the advancement of high-performance computing, full-waveform inversion has been increasingly applied to short-period body waves such as Pn. This approach incorporates full-wave finite-frequency sensitivity kernels and anisotropic parameterizations consistent with the elastic wave equation, allowing for high-resolution imaging of upper mantle azimuthal anisotropy. In this study, we perform a series of synthetic experiments using various testing models to qualitatively compare the performance of full-wave Pn inversion with that of conventional Pn travel-time tomography. Our results demonstrate that the waveform-based method improves the resolution and robustness in recovering both velocity and anisotropic parameters, particularly in identifying sharp gradients and deeper features. This study establishes the feasibility and advantages of full-wave Pn inversion for high-resolution azimuthal anisotropy imaging in tectonically complex upper mantle settings.